2015
DOI: 10.1093/eurheartj/ehv637
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of PCSK9 levels in patients with acute coronary syndromes

Abstract: In ACS patients, high initial PCSK9 plasma levels were associated with inflammation in the acute phase and hypercholesterolaemia, but did not predict mortality at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 31 publications
3
117
1
2
Order By: Relevance
“…Differences in PCSK9 levels during acute and stable periods have been reported [16], but few studies have focused on patients with AMI and the predictive value of the acute-phase plasma PCSK9 level for risk of recurrent CV events. One study assessed the association between PCSK9 and recurrent CV events in patients with ACS who presented within 5 days of pain onset [9]. Our study, however, was restricted to patients with AMI who provided samples within 24 h of symptom onset, which allowed us to assess associations between PCSK9 level during the acute phase and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Differences in PCSK9 levels during acute and stable periods have been reported [16], but few studies have focused on patients with AMI and the predictive value of the acute-phase plasma PCSK9 level for risk of recurrent CV events. One study assessed the association between PCSK9 and recurrent CV events in patients with ACS who presented within 5 days of pain onset [9]. Our study, however, was restricted to patients with AMI who provided samples within 24 h of symptom onset, which allowed us to assess associations between PCSK9 level during the acute phase and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few prospective studies [9-11] have considered the predictive value of plasma PCSK9 level for future CV events in patients with CVD, and these studies have produced inconsistent results. Two studies reported that circulating PCSK9 concentration predicted recurrent CV events in patients with stable coronary artery disease [10, 11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Mean PCSK9 in these 6 studies was 303 ng/mL and ranged from 94.3 to 546.5 ng/mL. Of the 7 studies included, only 1 reported all-cause mortality, 23 and the other studies reported CVD events including similar CVD outcomes. None of the 7 studies, however, reported associations between PCSK9 and the risk of discrete CVD events (e.g., cardiovascular mortality, myocardial infarction, stroke, or heart failure).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%